SOCIAL MEDIA MARKETING STRATEGIES: UNVEILING THE ROLE OF VALUE EQUITY AND BRAND EQUITY IN SHAPING PURCHASE INTENTION - Lovia Nurfaizi; Haditsa Nabila; Vina Akmalia; Muhammad Farrel Alfatih Alwin4; Akbar Riskal Amani; Aldriantara Sofyan (KOMITMEN: Jurnal Ilmiah Manajemen, 2026)
This study examines the influence of Social Media Marketing on Purchase Intention through the mediating roles of Brand Equity and Value Equity. Using data from 100 social media users in Bandung City, the study applies SEM-AMOS, heatmap correlation, and wordcloud analysis to assess structural relationships and consumer perception patterns. The findings show that Social Media Marketing positively strengthens Brand Equity and Value Equity, which subsequently influence Purchase Intention. Brand Equity demonstrates a stronger effect on Purchase Intention than Value Equity, indicating that brand recognition, trust, reputation, and loyalty are more dominant in shaping consumer buying decisions. Heatmap and wordcloud results further highlight the importance of engagement, interaction, content quality, trust, perceived value, and brand reputation. Overall, Social Media Marketing enhances purchase intention by building strong brand perception and customer-perceived value.